PENGEMBANGAN BUKU AJAR ILMU KEWARGANEGARAAN - Rinenggo, Alil; Karim, Abdul (Academy of Education Journal, 2023)
Lecturers have a special obligation to compile textbooks as a guide or source of student learning in the learning process. In practice, lecturers rarely develop textbooks so that the learning process runs less smoothly. The purpose of this study is to develop and determine the feasibility of textbooks in the Citizenship Science course. The research method uses R&D (Research and Development) by Borg and Gall. Data collection techniques using literature studies and questionnaires. Data analysis used descriptive qualitative and quantitative descriptive analysis techniques. The results showed that the results of the assessment from material experts obtained a percentage of 82.5% with the criteria of "Very Eligible", from media experts obtained a percentage of 93.05% with the criteria of "Very Eligible", small group trials obtained a percentage of 82.29% with the criteria of "Very Eligible", and the large group trials obtained a percentage of 85.278% with the criteria of "Very Eligible". The average percentage of the four assessments is 85.779% with the "Very Eligible" criteria.